Mapping the Star Formation and H i Gas Properties of Galaxies along Large-scale Structures around the Virgo Cluster - Hyein Yoon; O. Ivy Wong; Aeree Chung; Shan Huang (The Astrophysical Journal)
We investigate the star formation and neutral atomic hydrogen (H i ) gas properties of galaxies along three large-scale filaments and two galaxy groups in the wide field around the Virgo cluster. Our goal is to understand how galaxies are processed in low-density environments before falling into high-density regions. Combining the spatial distribution of galaxies with multiwavelength colors such as W3 − ​​​​​W1, NUV − r , and g − r , we find a predominance of blue galaxies across the structures, indicating normal-to-enhanced star formation, similar to that of isolated galaxies. However, one filament and one group show a significant number of red galaxies (32% and 20%, respectively), suggesting that star formation has been suppressed in low-density environments before reaching high-density regions. Intriguingly, these red galaxies span a wide range of stellar masses, and the presence of red dwarfs support that not only mass but also environment plays an important role in the quenching of star formation in cluster outskirts. One particular filament, potentially connected to Virgo, already has a group of red populations outside Virgo’s R _200 , making these galaxies good candidates for being “ preprocessed ” before entering the Virgo cluster. In addition, several galaxies in the filaments and groups possess relatively low H i gas contents, similar to cluster galaxies. However, the overall fraction of H i -deficient galaxies is not as significantly high as the fraction of red galaxies in these structures. This suggests that H i gas properties are less influenced by the environment than star formation properties in low-density regions, possibly due to gas replenishment through accretion.